2008
DOI: 10.1111/j.1468-0106.2008.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Nexus Between Housing and the Macro Economy: The Hong Kong Case

Abstract: This paper shows that, consistent with the 'economic base' theory, exports drive domestic consumption and domestic investment, but housing appears to serve as an important link between exports and domestic expenditures. Focusing on the Hong Kong economy, which is a small open economy with a big population, we found that exports and interest rates drive housing prices over a long period, while housing prices in turn drive domestic expenditures. Copyright 2008 The Authors. Journal compilation 2008 Blackwell Publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The impact of interest rates on real estate market has been extensively studied. Ho and Wong (2008) and Iacoviello (2005) found that interest rates have a significant impact on house price changes. Mishkin (2007) pointed out that monetary policy affects demand in real estate market through interest rate.…”
Section: Empirical Evidencementioning
confidence: 96%
“…The impact of interest rates on real estate market has been extensively studied. Ho and Wong (2008) and Iacoviello (2005) found that interest rates have a significant impact on house price changes. Mishkin (2007) pointed out that monetary policy affects demand in real estate market through interest rate.…”
Section: Empirical Evidencementioning
confidence: 96%
“…Levin and Pryce (2009) argued that UK house price increases over the period 1996-2007 were driven by real interest rates and Ho and Wong (2008) demonstrated that in Hong Kong house prices were driven by the local equivalent of the UK central bank base rate. Fitzpatrick and McQuinn (2007) also identified a long-run mutually reinforcing relationship between house prices and mortgage credit.…”
Section: Introduction Aims and Literaturementioning
confidence: 99%
“…Another channel linking housing prices and per-capita income is that when housing prices increase, many small and medium enterprises whose owners 13 It is recognized that there may be an endogeneity problem in the cointegration test involving HP and IPC. For this reason Ho & Wong (2008) used exports rather than IPC in their cointegration tests. However, other authors have done this test with HP and IPC and the same procedures are followed in this study with a realization that this is not quite satisfactory and has room for improvement.…”
Section: Results For Granger Causality Testsmentioning
confidence: 99%
“…Trichet (2003) also concluded that the macro-economy can be influenced by fluctuations in housing prices through wealth and balance-sheet effects on consumption and investment, while Peng, Yiu & Tam (2005) suggested that housing prices change can affect households' consumption spending through the wealth effect, as higher housing prices may signal faster growth of the economy and reduce households' financing constraints. Ho & Wong (2008) shared similar views, showing that housing prices drive domestic demand that consist of consumption and private investment.…”
Section: Theory Of Housing Price Determinationmentioning
confidence: 90%
See 1 more Smart Citation